RESPON PERTUMBUHAN DUA VARIETAS TANAMAN SELADA (Lactuca Sativa L.) AKIBAT PEMBERIAN DOSIS PUPUK ORGANIK CAIR (POC) LIMBAH RUMAH TANGGA DAN AB MIX YANG BERBEDA DENGAN SISTEM HIDROPONIK NFT - lailatul fazirah (AGRONISMA, 2021)
Lettuce (Lactuca sativa L.) is a horticultural commodity that has good value and prospects. One of the hydroponic systems that can be used for lettuce cultivation is the NFT (Nutrient Film Technique) system. AB mix nutrients that can be used in hydroponic systems are synthetic chemicals that contain very complete macro and micro nutrients for plants. An alternative method that can be used in hydroponic cultivation is to use Liquid Organic Fertilizer (POC) from household waste. This study aimed to determine the effect of differences in composition using AB mix and liquid organic fertilizer (POC) from household waste which gave the best effect on the growth and yield of two varieties of lettuce (Lactuca Sativa L.). The research was conducted at Green House Batu Urban Farming, Pesanggrahan village, Batu City, East Java. The study was carried out starting in December 2020 - January 2021. This study used a Randomized Block Design (RAK) as the environmental design, while the treatment design was a Split Plot Design consisting of the main plot (mainplot) and subplots (subplot). consisting of two factors with 3 replications. The parameters observed were plant height (cm), number of leaves (strands), total plant weight (g), plant dry weight (g), fresh weight consumed (g), harvest index (%). The mixing of POC doses into the AB mix nutrition in 2 varieties of lettuce did not give a real interaction on growth, but gave a real interaction on lettuce crop yields. The treatment dose of AB Mix 7.5 ml/L water + POC 31.25 ml/L water (N1) with the grand rapids (V1) variety had a significant effect on plant height, number of leaves and plant yields but was not significantly different from treatment N0 (AB Mix 10 ml/L water), and N2 (AB Mix 5 ml/L water + POC 62.50 ml/L water). While the red rapids (V2) variety had a significant effect and obtained the highest lettuce crop index value. The composition of household waste POC + AB mix which gave the best effect on the treatment The dose of AB Mix was 7.5 ml/L water + POC 31.25 ml/L water (N1) on the growth and yield of lettuce (Lactuca Sativa L.) .